2014
DOI: 10.1080/00140139.2014.897377
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based recommendations for building better bras for women treated for breast cancer

Abstract: , J. R. (2014). Evidence-based recommendations for building better bras for women treated for breast cancer. Ergonomics: an international journal of research and practice in human factors and ergonomics, 57 (5), 774-786.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
(47 reference statements)
0
18
1
Order By: Relevance
“…Little quantitative research has been conducted to understand the specific bra needs of women with reconstructed breasts, but qualitative studies have shown that breast cancer patients have common complaints and challenges pertaining to bra comfort and fit [7], [8]. From focus groups and an online survey our team conducted in 2014, we learned that women with breast reconstruction had difficulty finding post-surgical garments that addressed their specific needs [8].…”
Section: Fig 1 Significant Morphological Changes Occur After Breastmentioning
confidence: 99%
“…Little quantitative research has been conducted to understand the specific bra needs of women with reconstructed breasts, but qualitative studies have shown that breast cancer patients have common complaints and challenges pertaining to bra comfort and fit [7], [8]. From focus groups and an online survey our team conducted in 2014, we learned that women with breast reconstruction had difficulty finding post-surgical garments that addressed their specific needs [8].…”
Section: Fig 1 Significant Morphological Changes Occur After Breastmentioning
confidence: 99%
“…In clothing industry, the aim is either mass customization for upper body (every day and sports) underwear and clothing according to sizing standards, or for made-to-measure (personal customization) [10] e.g. in post-surgery compression bras [11]. European Standard DIN EN 13402-3:2017-12 [12] requires only underbust and bust circumference for bra size designation.…”
Section: Introductionmentioning
confidence: 99%
“…However, breast cancer mortality rates for women have decreased by 19% over the last decade (New Zealand Guidelines Group, 2009). This is attributed to a multitude of factors including increased public awareness, earlier detection rates, and greater effectiveness of adjuvant treatment (Gho et al, 2014). With the extensive advances being made in the medical field, breast cancer survivors are living longer than ever before (Gho et al, 2014).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…This is attributed to a multitude of factors including increased public awareness, earlier detection rates, and greater effectiveness of adjuvant treatment (Gho et al, 2014). With the extensive advances being made in the medical field, breast cancer survivors are living longer than ever before (Gho et al, 2014). However, despite the positive survival rates, undesired appearance-related side effects such as loss of breasts, tissue damage, deformities in the breast, decreased range of motion, lymphedema, weight gain, muscle loss, and weakness are frequently reported (Collins et al, 2011;Irwin et al, 2005).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation